Construction of Electrochemical Aptamer Sensor Based on Pt-Coordinated Titanium-Based Porphyrin MOF for Thrombin Detection - Jiang, Jiazi; Cai, Quan; Deng, Minghan (Frontiers in Chemistry, 2022)
In this work, a Pt-coordinated titanium-based porphyrin metal organic framework (Ti-MOF-Pt) was prepared by embedding single-atom Pt through strong interactions between the four pyrrole nitrogen atoms in the rigid backbone of the porphyrin. The synthesized Ti-MOF-Pt was characterized by TEM, XRD, FTIR and BET. Then, the Ti-MOF-Pt has been used for glassy carbon electrode surface modification and consequently used for construction of a thrombin aptamer sensor. The high surface area provides by MOF and excellent electrochemical property provided by Pt enhance the sensing performance. After optimization of amount of aptamer, hybridization time and specific reaction time, the fabricated aptamer sensor exhibited a linear relationship with the logarithm of the thrombin concentration in the range of 4 pM to 0.2 μM. The detection limit can be calculated as 1.3 pM.